ANALISIS YURIDIS TENTANG GUGATAN TIDAK DAPAT DIEKSEKUSI (NON-EXECUTABLE) DALAM PUTUSAN NOMOR : 23/Pdt.GS/2023/PN Idm - Jaya, Mardi; Prawesti, Wahyu; Ayuningtiyas, Fitri; Damayanti, Sri Sukmana (Gapenas Publisher, 2025)
Court decisions in civil cases should provide legal certainty and restoration of rights for the winning party. However, in practice, decisions that cannot be enforced (non-executable) are often found, resulting in substantive justice failing to be realised. This phenomenon raises serious questions about the effectiveness of the judicial system, particularly in the context of dispute resolution through simple lawsuit mechanisms. This study stems from the urgency to examine the problem of unenforceable judgments, focusing on Judgment Number 23/Pdt.GS/2023/PN.Idm, in which, although the breach of contract lawsuit was granted, the verdict was not condemnatory, so enforcement could not be carried out. The main objective of this study is to analyse the legal provisions regarding unenforceable lawsuits and assess the extent to which the decision provides legal protection for the plaintiff. The research questions focus on two things, namely how the law regulates non-executable decisions and whether Decision Number 23/Pdt.GS/2023/PN.Idm has fulfilled the principle of legal protection. The research method used a normative legal approach with a case law approach. The primary legal materials were laws and regulations and court decisions, while the secondary legal materials included legal literature and expert opinions. Data was collected through literature study and analysed qualitatively with an emphasis on legal interpretation and systematic logic. The results of the study show that non-executable decisions are generally caused by weaknesses in declarative decisions, ambiguity in the subject matter of the dispute, or the subject matter being tied to a third party. The Indramayu case confirms the gap between formal legality and substantive justice. The conclusion of the study emphasises the need for clear and operational formulation of verdicts, evaluation of simple lawsuit regulations, and an increased role for judges and advocates in ensuring the effectiveness of legal protection. Further research is recommended to examine similar cases across regions to identify national patterns